Accounts demystified : the astonishingly simple guide to accounting - Rice, Anthony (Prentice Hall Business, 2011)
An astonishingly simple guide to the fundamental principles of accounting, written specifically for those without a financial background. Simple, easily absorbed and clearly explained, this book will guide you through all the major accounting concepts. You will learn how to master company accounts, understand balance sheets, profit and loss accounts and cash flow systems and how to analyse and monitor your company's financial performance. This new edition is updated throughout to incorporate changes in accounting regulations and includes a new chapter on keeping personal accounts. Whether you manage a small company, are a trainee accountant, an entrepreneur, a business studies or MBA student, an investor on the stock market or a manager in a big corporation, you will not want to be without this definitive and user-friendly guide to the fundamental principles of accounting.